The Analysis of Challenges in the Pronunciation of English Consonants Faced by English Education Students and English Literature Students of UIN Maulana Malik Ibrahim - Muhammad Raudlatul Hidaytullah; Abbas Rifai; Wahyu Indah Mala Rohmana (Jurnal Bahasa, Sastra, dan Studi Amerika, 2024)
This study investigates the pronunciation challenges of English consonants among English Education (EE) and English Literature (EL) students at UIN Maulana Malik Ibrahim Malang. Employing a qualitative descriptive method, data were collected from ten students (five from each program) through pronunciation tests and audio recordings. The analysis focused on common errors in consonant sounds such as /θ/, /ð/, /ʒ/, and /ʃ/. Results reveal that EE students struggle primarily with interdental fricatives (/θ/ and /ð/), often substituting them with /t/ and /d/. Meanwhile, EL students face greater challenges with voiced fricatives (/ʒ/ and /z/), substituting them with /s/ or /ʃ/. Both groups showed shared difficulties with palatal fricatives, indicating gaps in phonetic proficiency. These findings highlight the influence of curriculum focus, with EE students benefiting more from phonetics training, whereas EL students emphasize textual analysis. The study underscores the importance of targeted pronunciation interventions to address department-specific needs and improve linguistic proficiency among learners.